2016
DOI: 10.1002/anie.201610371
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of the NH−NH Bond Triggered by Potassium tert‐Butoxide in Liquid Ammonia

Abstract: A novel strategy for the dehydrogenation of the NH-NH bond is disclosed using potassium tert-butoxide (tBuOK) in liquid ammonia (NH ) under air at room temperature. Its synthetic value is well demonstrated by the highly efficient synthesis of aromatic azo compounds (up to 100 % yield, 3 min), heterocyclic azo compounds, and dehydrazination of phenylhydrazine. The broad application of this strategy and its benefit to chemical biology is proved by a novel, convenient, one-pot synthesis of aliphatic diazirines, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…Components bearing N]N bonds are ubiquitous motifs in therapeutic agents, food additives, dyes, pigments, photochemical switches, and radical reaction initiators. [32][33][34] A previous report using tBuOK was conducted in liquid ammonia which is dangerous and need to operate at À75 C. 35 On the contrary, simply sealed the starting material in a pressure tube and heat at 60 C we can obtain 95% azobenzene from hydrazobenzene. Then a series of aromatic azo compounds were successfully prepared in excellent yields in short reaction time ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Components bearing N]N bonds are ubiquitous motifs in therapeutic agents, food additives, dyes, pigments, photochemical switches, and radical reaction initiators. [32][33][34] A previous report using tBuOK was conducted in liquid ammonia which is dangerous and need to operate at À75 C. 35 On the contrary, simply sealed the starting material in a pressure tube and heat at 60 C we can obtain 95% azobenzene from hydrazobenzene. Then a series of aromatic azo compounds were successfully prepared in excellent yields in short reaction time ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent oxidation to the diazirine can occur under similar conditions to those discussed above.M ost recently,b ase promoted oxidations of the diaziridine using molecular oxygen (O 2 )i nt he form of air have been reported, and, in certain cases, have allowed the combination of steps into ao ne-pot protocolfor the synthesis of alkyl diazirines. [22] In addition to improved procedures for the synthesis of diazirines, growing awareness of their compatibility with common functional group interconversions has led to their increased use in multi-step synthetic sequences. In the particularc ase of TPDs, these include ag eneral insensitivity towards strong acid or base, enabling base promoted alkylationreactions as well as Lewis acid mediated electrophilic aromatic substitution.…”
Section: Traditional Synthesis Of Diazirinesmentioning
confidence: 99%
“…18 Therefore, it is important to precisely optimize the synergistically active metal sites and N-doped porous structures simultaneously over carbon-based catalysts for better exposure in dehydrogenation reactions. [19][20][21] In 2010, Titirici and coworkers described the hydrothermal treatment of chitosan, followed by calcination, for the preparation of carbonaceous materials. 22 Later, it was shown that chitosan could serve as an excellent precursor to generate Ndoped graphene.…”
Section: Introductionmentioning
confidence: 99%